Azido‐Alkynes in Gold(I)‐Catalyzed Indole Syntheses. Issue 12 (8th September 2021) - Greiner, Luca C.; Matsuoka, Junpei; Inuki, Shinsuke; Ohno, Hiroaki
Abstract: The exploitation of nitrogen‐functionalized reactive intermediates plays an important role in the synthesis of biologically relevant scaffolds in the field of pharmaceutical sciences. Those based on gold carbenes carry a strong potential for the design of highly efficient cascade processes toward the synthesis of compounds containing a fused indole core structure. This personal account gives a detailed explanation of our contribution to this sector, and embraces the reaction development of efficient gold‐catalyzed cascade processes based on diversely functionalized azido‐alkynes. Challenging cyclizations and their subsequent application in the synthesis of pharmaceutically relevant scaffolds and natural products conducted in an intra‐ or intermolecular fashion are key features of our research. Abstract : Gold‐catalyzed cascade cyclizations of azido‐alkynes provide facile access to a variety of fused indole derivatives, including indoloquinolines, benzo[ c ]carbazoles, pyrrolo[2, 3‐ c ]carbazoles, and benzannulated medium‐ring fused indoles. These reactions proceed through the formation of highly reactive α‐imino gold(I) carbenes, which efficiently undergo intramolecular allylation, cyclopropanation, and arylation.